Proposta de aplicação do Balanced Scorecard para o operador de transporte ferroviário - Frederico, Guilherme Francisco [UNESP] (2008)
The Brazilian railroad transport has been achieving a continuous growth, in terms of its production in the last years, mainly after the beginning of the network concessions to private initiative. However, when comparing the participation of the Brazilian railroad modal, towards other countries, in the transports matrix, Brazil still has a low level of participation in this kind of modal. The increase this participation, through of the continued growth will be relevant for the development of the country, due to the necessity of a bigger external competitiveness of our products, which can be achieved by the reduction of its overall logistics costs. Thus, the railroad transport operators may need to make changes in the ways of managing the performance of its operations, searching up achieving the strategical objectives of medium and long term and also to promote the continuous improvement of its outcomes in view other perspectives, beyond financial, traditional measure of performance in the organizational environment. From this scenery, this work has for objective to propose a model of the system of performance measurement for application in the railroad transport operators, which was built through of a case study made in a company of this sector, seeking to establish a typical structure of analysis, and also, by alignment of its common strategical objectives. Thus, searched up the Balanced Scorecard - BSC like option of performance measurement system to be used by these organizations, due to its strategical function and also of improvement instrument, having four perspectives of performance measurement (financial, customer, internal processes and learning and growth), besides having a relation of cause and effect between them, as the guidance of a strategical map.